Interlocking Directorship and Corporate Performance - Norhaniza, Saidin (2011)
The issues of corporate performance and interlocking directorships have received considerable attention. Therefore, the objective of this study is to examine the effects of interlocking directorships on corporate performance. Using data from listed companies both on Main and Second board of Bursa Malaysia in 2007, the result shows that interlocking directorships have a significant positive effect on corporate performance. The finding supports the resource dependence theory and postulation that multiple directorships enhance directors' expertise and increased director's motivation in discharging their responsibility.